Analisis Bangkitan Perjalanan Penduduk pada Perumahan Yayasan Pegawai Kantor Gubernur Makassar Sulawesi Selatan - Hilioni Felisitas Dengen; Rais Rachman; Lasty Dinulfy (Program Studi Teknik Sipil UKI Paulus-Makassar, 2023)
Housing Foundation for the Office of the Governor of Makassar Employees of South Sulawesi Biringkanaya Subdistrict, Paccerakkang Village. The population of the housing complex Yayasan Pegawai Kantor Gubernur Makassar South Sulawesi is 3,800 people The travel departure of a group of residents of the South Sulawesi Governor's Office Employee Foundation housing estate will cause traffic congestion. The purpose of this study was to identify household and travel characteristics of the Yayasan Pegawai Kantor Gubernur Makassar South Sulawesi housing estate and model the travel demand. The survey was participated by respondents who filled out questionnaires on an online-based formula. Data analysis used statistical methods such as descriptive correlation and multiple linear regression tests. The research results show that the factors that influence travel demand in the Makassar Governor's Office Employee Foundation of South Sulawesi are the number of household members (X1) and travel time (X8) to the quantity of generation (Y). The equation of travel demand in the housing of Yayasan Pegawai Kantor Gubernur Makassar South Sulawesi is Y = 1.096-0.116X1+0.130X8, the coefficient of determination (R2) is 18.1%.